(untitled) (Biological Sciences - PJSIR, 2001)
Nimbokil-60 EC, an expelled neem (Azadirachta indica A. Juss) seed oil based insecticide was tested to determine its mammalian toxicity. Tests for acute and percentaneous toxicity, acute inhalation, skin and eye irritation, sub-chronic effects and effect on fertility were carried out. Results revealed that ’Nimbokil’ had no adverse or ill effects on the test animals under administered doses. LD-50 was found to be 16 ml kg" body-weight of the animals. Autopsy observation showed no gross changes in vital organs i.e. heart, lungs, liver, ovary and testicles of the test animals. When applied as such (100% concentration) completely within 72 h. However, at lower concentrations, no eye irritation was noticed. It is therefore, concluded that Nimbokil-60EC be classified as non-toxic’.